The Effectiveness of VILCON'S Blended E-Learning Model in the Covid-19 - Mufidah Mufidah; Nurul Kami Sani; Nuraini Nuraini; Nurul Fitri Aras (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Along with development existing technology , implementation from Internet use for learning one of them is e-learning. On the situation the Covid 19 pandemic required online learning . Applied online learning No free from objective same learning . As partners and facilitators, lecturers demanded selecting and processing the learning process , so need consider the use of appropriate learning models with characteristics eye college. Selection of the learning model used influential to quality and yield learning. Study This held in framework test the effectiveness of the ViLCon blended e-learning model that has been developed in offline or online learning so learning going on with effective and efficient so that objective Study reached. Study This including quasi- experimental research . Research design experiment used in study is a one group pre-test post-test design. test used has analyzed its validity with tested validity and reliability. Validity test carried out on 40 students class A validity test instrument form question choice double. For measurement done with use help SPSS application. Score average test initial (pretest) understanding draft student before learning is of 38.33% of ideal score and percentage average posttest score of 74.63% of ideal score . Meaningfulness enhancement from percentage average pretest and posttest scores can represented by the average normalized gain that is of 0.59. If confirmed in category from Hake (1999), then results enhancement the including in category medium. this show that use of the VilCon Blended E-learning learning model effective in increase understanding draft students in lecture learning models math. Based on analysis the results and discussions that have been studied outlined can concluded that module VilCon Blended E-Learning learning in learning model lectures mathematics effective used For increase results learning and motivation Tadulako University PGSD student.